2013
DOI: 10.3109/13693786.2012.685767
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fungal-specific fluorescent labeled echinocandin probes as diagnostic adjuncts

Abstract: The diagnosis of invasive fungal infections from radiographic imaging is non-specific and problematic. As a first step toward increasing specificity, we describe the development of a broad-spectrum fungal-specific targeting molecule, which when modified with a fluorescent label fully retains its targeting properties, and provides a basis for future imaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…Because loss of CDC50 is expected to perturb membrane function, we hypothesized that the cdc50Δ mutant may exhibit enhanced sensitivity to caspofungin because it alters drug uptake into cells. To test this hypothesis, we monitored drug uptake by using boron dipyrromethene difluoride (BODIPY)-labeled caspofungin ( 25 ). We observed that while H99 failed to take up significant amounts of fluorescently labeled caspofungin, producing only limited intracellular fluorescence, the cdc50Δ mutant showed a significantly higher level of fluorescent signal, indicative of an increased intracellular drug concentration ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because loss of CDC50 is expected to perturb membrane function, we hypothesized that the cdc50Δ mutant may exhibit enhanced sensitivity to caspofungin because it alters drug uptake into cells. To test this hypothesis, we monitored drug uptake by using boron dipyrromethene difluoride (BODIPY)-labeled caspofungin ( 25 ). We observed that while H99 failed to take up significant amounts of fluorescently labeled caspofungin, producing only limited intracellular fluorescence, the cdc50Δ mutant showed a significantly higher level of fluorescent signal, indicative of an increased intracellular drug concentration ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations were noted in the 5’-upstream region of CYP51 , and in the coding regions of other genes linked with ergosterol biosynthesis (Supplementary Figure S1 ). However, these did not affect the intracellular level of CYP51, as judged by binding between the enzyme and posaconazole conjugated with the fluorophore boron-dipyrromethene 36 , 37 (Supplementary Figure 2 ). To exclude the possibility that TcNTR-1 depletion might perturb susceptibility to posaconazole, we tested its activity against two cloned T. cruzi cell lines (Methods) in which we had deleted one copy of the gene (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Conjugation of CSF with a fluorophore was performed as described previously. 9 Briefly, CSF-DDAO conjugate was produced by incubating 20 mg (15 μmol) of CSF-diacetate and 2.8 mg (8 μmol) of DDAO-isothiocyano derivative in 0.2 ml of dimethylformamide and 4 μl of triethylamine at 50°C during 30 min. Thin liquid chromatography (TLC) analysis in acetonitrile-water (7:1) developing system revealed nearly complete conversion of the original DDAO derivative (Rf = 0.95) to the main reaction product (Rf = 0.6), which was purified by preparative TLC in the same system.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that CSF can be modified at the ethylenediamine functionalized position with a reporter BODIPY, while still retaining highly potent antifungal targeting properties. 9 When coupled with the fluorophore label 7-Amino-9H-(1,3-Dichloro-9,9-Dimethylacridin-2-One) (DDAO) at the amino group of 3-hydroxyornithine residue, CSF-DDAO can be used as fungal specific probe, whereby drug-bound cells fluoresce and can be visualized by near-infrared (NIR) fluorescence imaging. Furthermore, a liposome-encapsulated CSF-DDAO (L-CSF-DDAO) was developed to facilitate a greater penetration of the probe into the cornea and to minimize its interaction with corneal cell membranes.…”
Section: Introductionmentioning
confidence: 99%